2016
DOI: 10.1152/ajprenal.00121.2014
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pathways for angiotensin II production as an important determinant of kidney damage in endotoxemia

Abstract: Sepsis is an uncontrolled systemic inflammatory response against an infection and a major public health issue worldwide. This condition affects several organs, and, when caused by Gram-negative bacteria, kidneys are particularly damaged. Due to the importance of renin-angiotensin system (RAS) in regulating renal function, in the present study, we aimed to investigate the effects of endotoxemia over the renal RAS. Wistar rats were injected with Escherichia coli lipopolysaccharide (LPS) (4 mg/kg), mimicking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
10
0
2
Order By: Relevance
“…Our results showed that there was no alteration of ACE activity, but increased chymase activity in FG in renal tissues, that associated with elevated Ang II concentrations suggest that alternative pathways were activated to produce this peptide, as has been shown to occur in the kidney under toxemia as described by Rosa et al (2016) . We can also confirmed that the enzymes tonin, cathepsin, and chymase are involved in this increase in Ang II levels ( Rosa et al, 2016 ). In our high fructose model of kidney damage, we believe that these enzymes may also be responsible for the high Ang II levels.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results showed that there was no alteration of ACE activity, but increased chymase activity in FG in renal tissues, that associated with elevated Ang II concentrations suggest that alternative pathways were activated to produce this peptide, as has been shown to occur in the kidney under toxemia as described by Rosa et al (2016) . We can also confirmed that the enzymes tonin, cathepsin, and chymase are involved in this increase in Ang II levels ( Rosa et al, 2016 ). In our high fructose model of kidney damage, we believe that these enzymes may also be responsible for the high Ang II levels.…”
Section: Discussionsupporting
confidence: 57%
“…The samples were extracted using C 18 Sep-Pak columns and analyzed by HPLC. The peptide was separated by HPLC (Shimadzu System; Kyoto, Japan) using an Aquapore reversed-phase column (250 mm × 4.6 mm; ODS 300; 7 μm; PerkinElmer; São Paulo, São Paulo, Brazil), using a linear gradient (5–35%) of the mobile phase B (95% acetonitrile in 0.1% H 3 PO 4 ) at a 1.5 mL/min flow rate (40 min) ( Rosa et al, 2016 ). The HPLC column was calibrated under the same conditions using synthetic standards, and the peptides angiotensin I (Ang I), angiotensin II (Ang II), and angiotensin 1-7 (Ang 1-7) were detected with absorbance (l = 214 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Angiotensins were extracted from the LV and plasma as previously described [ 22 , 23 ]. LV tissue was weighed and homogenized with 100 mmol/L PB, pH 7.2, containing 340 mmol/L sucrose, 300 mmol/L NaCl and a mix of proteases inhibitors (Complete Mini Roche).…”
Section: Methodsmentioning
confidence: 99%
“…We have similarly reported significant increases in renal arteriolar chymase-dependent ANG II formation in diabetic compared to control mice (Park et al, 2013), and functional evidence for enhanced chymase-dependent renal microvascular vasoconstriction (Harrison-Bernard et al, 2013;Park et al, 2010). We speculate that cathepsin G (Rosa et al, 2016), kallikrein, tonin, and elastase-2 may represent alternative pathways for angiotensin-converting enzyme-independent ANG II formation in this study (Uehara, Miura, & Yahiro, 2013). These findings are potentially of great relevance to the treatment of patients.…”
Section: Discussionmentioning
confidence: 52%